Development of a protection motivation theory based questionnaire for measuring parental digital security practice in Malaysia / Muhd Zulfadli Hafiz Ismail - Muhd Zulfadli Hafiz, Ismail (2020)
Knowledge on parental digital security, which is the parental practice of maintaining the safety of their children online, is crucial to produce good digital citizens. Protection motivation theory (PMT) is a useful theoretical model for explaining protective behaviour and understanding this practice. Many studies and tools for exploring protective behaviour have been produced based on PMT, but there is no assessment tool available for assessing parents’ digital security practice in the Malaysian context. Thus, the development of an assessment tool that reflects Malaysian parents’ digital security practice based on established frameworks such as the PMT is essential. Therefore, this study attempted to develop a PMT-based instrument for measuring the digital security practice of Malaysian parents and to explain the factors that determine these practices based on the PMT domains. The study was conducted over 2 years from January 2018 to December 2019. It consisted of three major phases: item development, scale development and scale evaluation. Item development consisted of domain identification, item generation, content validity and translation, and involved a systematic review of the literature and engagement with experts and stakeholders. Scale development focused on pretesting, test-retest reliability and pilot testing for exploratory factor analysis. Scale evaluation involved path analysis of the domains and confirmatory factor analysis. The scale development and scale evaluation phases involved Malaysian parents with children below 18-years-old who were selected through purposive sampling, which involved two government clinics in Selangor, three private clinics, one each in Selangor, Perlis and Sabah, and three workplaces in the Klang Valley. The output item development was a bilingual 54-item questionnaire covering seven domains: perceived susceptibility, perceived severity, perceived self-efficacy, perceived response efficacy, perceived maladaptive reward, perceived response cost and parental digital security practice. Scale development resulted in three items being dropped due to poor reliability and poor iv loading, and nine domains: perceived susceptibility, perceived severity, perceived selfefficacy, perceived response efficacy, perceived tangible cost, perceived psychological cost, perceived maladaptive reward, discursive digital security practice and control digital security practice. In the scale evaluation phase, the remaining 51 items showed good discriminant and convergent validity, and both measurement and structural model assessment of the domains were adequate. Further analysis revealed that perceived selfefficacy (β= 0.30, p < 0.001), perceived response efficacy (β= 0.20, p=0.01) and perceived maladaptive reward (β=-0.20, p < 0.001) to be significant determinants of parental digital security practice. The model was able to explain 34% variation of parental digital security practice. The study contributes to knowledge by producing a validated instrument for measuring parental digital security practice in Malaysia. It also identifies the major determinants of parental digital security practice based on the PMT domains. The validated instrument has the potential to be utilised further to understand cyber parenting practices in general. The study also highlights that efforts need to be made to improve parental efficacy and reduce their perceived maladaptive rewards to keep their children safe online because these factors have a major influence on the effectiveness of parental digital security practice. Keywords: Cyber parenting, digital, citizenship, security, protection motivation theory.